Development of smart monitoring system using IOT - Nsaif, Waleed Khalid (2020)
This research project is about the design and implementation of weather monitoring with automation control. The additional feature added in like security will help to protect the system. The general idea behind the project is to provide temperature and humidity readings, appliances control plus the security. All the systems are controlled using IoT technology. The designed system consists of microcontroller as a main component, the humidity & temperature sensor as well as the ultrasonic sensor. The humidity and temperature sensor constantly detect the humidity and temperature of surrounding. The sensor output signals are read by the microcontroller. The microcontroller process the signals and send the signal over an internet network via a WiFi module called, ESP8266. There is another sensor which is ultrasonic sensor also produce digital signal when detecting a mobile object. All the signals are send at the same time to the ESP8266 WiFi module. At the receiver, there will be a platform or Apps designed to display those signals. Typical Apps used is Blynk. By using this Apps, the information from the sensor not only can be displayed but also saved in a database. Keywords: weather monitoring, automation control, security system, humidity & temperature sensor, ultrasonic sensor and Apps.